Multifaceted bioactivity of brown seaweed-derived fucoidan from the Indian Coastline: A natural health product candidate - Manisha Prajapati; Dharmendra Kumar; Shivankar Agrawal; Dhiraj Kumar; Pooja Baweja; Dinabandhu Sahoo (PLoS ONE, 2026)
Brown seaweeds are rich in bioactive constituents, among which fucoidan a sulphated polysaccharide is particularly noted for its broad-spectrum therapeutic properties. This study explores the multifaceted bioactivity of fucoidan extracted from six brown seaweed species ( Sargassum wightii , Sargassum tenerrimum , Sargassum cinereum , Turbinaria conoides , Padina boergesenii , and Padina tetrastromatica ) collected from the Pudumadam coast, Gulf of mannar region, Tamil Nadu, India. Fucoidan was isolated and structurally characterized using Fourier-transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy. The antioxidant capacity of the extracts was assessed through 2,2-diphenyl-1-picrylhydrazyl (DPPH), hydroxyl radical scavenging activity (HRSA), and ferric reducing antioxidant power (FRAP) assays, with Sargassum cinereum showing the highest antioxidant activity (IC₅₀: 0.342 ± 0.01 mg/ml for DPPH; 1.26 ± 0.02 mg/ml for HRSA; 33.17 ± 0.02 mM Fe (II)/g for FRAP). In vitro antidiabetic assays demonstrated that fucoidan from Sargassum wightii exhibited the strongest inhibition of α-amylase and α-D-glucosidase (IC₅₀: 0.042 ± 0.02 mg/ml). Additionally, fucoidan from S. wightii displayed significant cytotoxic activity against MCF-7 human breast cancer cells. These findings underscore the therapeutic promise of brown seaweed-derived fucoidan as a multifunctional agent, supporting its potential application in the formulation of natural health products.